Broadband VHF lightning radiation sources localization by ESPRIT algorithm - Du, Shuangjiang; Shi, Lihua; Qiu, Shi; Duan, Yantao; Li, Yun; Sun, Zheng (Atmospheric research, 2025)
Fast and fine radiation source localization algorithm is of vital importance to lightning warning and protection. Current high-accuracy localization techniques, such as the time reversal technique (TR) and the multiple signal classification (MUSIC), are based on traversal search mechanism, which takes a long time. In this paper, the estimation of signal parameters via rotational invariance technique (ESPRIT) is applied to lightning radiation source localization, and the direction of arrival (DOA) can be directly solved through the covariance matrix, so it is very efficient. For the broadband VHF signal, the incoherent signal method (ISM) is combined with ESPRIT. Two classical structures of uniform L-shaped array and uniform circular array are studied and applied to ESPRIT algorithm. As for the uniform circular array, the fourth order cumulant matrix is constructed to find the translation invariant subarrays. To unwrap the phase ambiguity caused by the calculated phase angle of ESPRIT algorithm, the total least difference of slope (TLDS) principle is proposed. The proposed ESPRIT algorithm is more than 1400 times faster than MUSIC while its localization accuracy is still pretty high, which is able to detect the radiation source under -8 dB signal to noise ratio (SNR) according to the result of numerical simulations, and can map continuous and fine lightning development channel in the experiments on the measured lightning data.